2023
DOI: 10.3389/fphys.2023.1217183
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of two-hit models of acute and ventilator-induced lung injury on lung structure, function, and inflammation

Abstract: Acute respiratory distress syndrome (ARDS) and acute lung injury have a diverse spectrum of causative factors including sepsis, aspiration of gastric contents, and near drowning. Clinical management of severe lung injury typically includes mechanical ventilation to maintain gas exchange which can lead to ventilator-induced lung injury (VILI). The cause of respiratory failure is acknowledged to affect the degree of lung inflammation, changes in lung structure, and the mechanical function of the injured lung. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Comparison to manual classification ( Figure 1 ) shows that the sensitivity for ‘injury’ pixels was 0.78, indicating that automated segmentation and the morphological post-processing steps accurately describes ‘injury’ pixels, while the specificity of 0.85 indicates that most non-injury pixels are correctly excluded. In a prior study a different observer (BJS) performed manual morphometry (stereology) on the same samples ( Bilodeaux et al, 2023 ) and found that the percentage of collapsed septal tissue in the entire lung was 14.55% for LAV and 2.28% for CTRL. In the current study the automated approach yielded 19.82% in the LAV group and 9.88% in the CTRL group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison to manual classification ( Figure 1 ) shows that the sensitivity for ‘injury’ pixels was 0.78, indicating that automated segmentation and the morphological post-processing steps accurately describes ‘injury’ pixels, while the specificity of 0.85 indicates that most non-injury pixels are correctly excluded. In a prior study a different observer (BJS) performed manual morphometry (stereology) on the same samples ( Bilodeaux et al, 2023 ) and found that the percentage of collapsed septal tissue in the entire lung was 14.55% for LAV and 2.28% for CTRL. In the current study the automated approach yielded 19.82% in the LAV group and 9.88% in the CTRL group.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a secondary analysis of images generated in previously reported experiments ( Bilodeaux et al, 2023 ) and the key experimental details are summarized below. The study was conducted on female C57/BL6 mice, aged seven to 10 weeks, and was approved by the University of Colorado Denver Institutional Animal Care and Use Committee (IACUC) under protocol #00230.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cannula was connected to the FlexiVent, controlled mechanical ventilation started with a respiratory rate of 150 breaths per minute, tidal volume 10 ml/kg and inspiratory-to-expiratory time ratio 1:2. A series of different ventilation maneuvers for lung mechanical measurements were performed based on published methodology 11 . Measurement blocks (derecruitability tests) were carried out as PEEP was sequentially decreased from 12, 8, 5, 3 and finally to 0 cmH 2 O (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The load of microatelectases might at least be reduced partially by maintaining an appropriate PEEP. However, both efficiency and pressure ranges needed for recruitability depend on the underlying etiology and pathophysiology 11 . At the alveolar level, three different populations of alveoli have been described during lung injury: (1) One population is characterized by alveolar flooding or irreversible collapse and is not recruitable; (2) a second cohort is unstable and derecruitment can be avoided by appropriate PEEP; (3) the third population appears to be healthy and remains open even at low airway opening pressures 12 .…”
Section: Introductionmentioning
confidence: 99%